Towards common European audio description guidelines: Results of the Pear Tree Project - Mazur, Iwona; Chmiel, Agnieszka (My University, 2012)
The article reports on the Pear Tree Project (PTP), conducted as part of the Media for All project whose original aim was to develop audio description (AD) guidelines in Europe in order to ensure consistent high quality AD. However, before streamlining AD standards, a number of issues had to be addressed, the most essential one being whether relevant cross-linguistic and cross-cultural differences in Europe are insignificant enough to enable the development of such common European AD guidelines. In order to answer these questions a methodology proposed by Chafe (1980) concerning the way representatives of various cultures and languages perceive and describe moving images was adopted by a group of AD researchers in the PTP. Participants from various countries were asked to watch a short film and recount what they saw. The data were then subjected to comparative lexical, discourse and narrative analysis in order to uncover both similarities and differences in the processing of visual information by representatives of the languages and cultures concerned. The results and their analysis will be presented in the paper on the basis of which the authors will attempt to provide an answer to the question of whether creating common European audio description guidelines is feasible.
Keywords: audio description; media accessibility; AD guidelines; film perception